2016
DOI: 10.1371/journal.pone.0160805
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Health Perception in Aging: Do Body Mass and Satisfaction Matter? A Three-Path Mediated Link

Abstract: Although ageing people could benefit from healthy diet and physical activity to maintain health and quality of life, further understandings of the diet- and physical activity-related mechanisms that may cause changes in health and quality of life perception are necessary. The purpose of the study was to investigate the effect of eating attitudes, body mass and image satisfaction, and exercise dependence in the relationship between physical activity and health and quality of life perception in older individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 49 publications
4
40
0
3
Order By: Relevance
“…However, the BMI of eleven newly recruited senior orienteering athletes enrolled in an additional study was found to be normally distributed with a mean value of 23.8 ± 3.2 Std. This is in accordance with a recent study showing a lower BMI value of senior athletes compared to general older adults [ 45 ]. Hence, these findings indicate that the increased zonulin levels in the present study were not a result of overweight/obesity or cardiovascular disease.…”
Section: Discussionsupporting
confidence: 94%
“…However, the BMI of eleven newly recruited senior orienteering athletes enrolled in an additional study was found to be normally distributed with a mean value of 23.8 ± 3.2 Std. This is in accordance with a recent study showing a lower BMI value of senior athletes compared to general older adults [ 45 ]. Hence, these findings indicate that the increased zonulin levels in the present study were not a result of overweight/obesity or cardiovascular disease.…”
Section: Discussionsupporting
confidence: 94%
“…In our study, realistic managers and underestimators performed the highest number of weekly hours of leisure time activities and vice versa for the overestimators. The observation that physically active participants or managers with an athletic background showed greater ability to perceive their health status than inactive participants is in line with previous scientific reports (Condello et al 2016, van Weering et al 2011. Furthermore, participants' socio-economic backgrounds may have influenced their ability to produce a realistic self-perception (Jung et al 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Since including too many variables in the model for LCA could negatively affect the analysis, a total of 18 variables (included in Table 1 ) out of the 87 items contained in the ASSO questionnaires were selected and gathered into the following three dimensions: (1) biological and genetic; (2) sociocultural and environmental; (3) life habits. The inclusion of items in the different dimensions was based on previous literature suggesting risks within the context of a larger conceptual framework for health characteristics and for sedentary behaviours [ 50 , 51 , 52 ] and subsequently was adapted to fitness.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, among these factors, a total of eleven latent class indicators were chosen to represent multiple dimensions of fitness risks, i.e., biological (health risk/status) and lifestyle (physical activity/sedentariness, alcohol/smoking, and meal patterns and habits) dimensions; the other seven variables were investigated in a multivariate analysis for their role as possible predictors of class membership (gender, age, having at least one parent overweight/obese, parents’ education, family affluence scale (FAS), town of residence’s size, and school type) [ 50 , 51 , 52 , 53 ].…”
Section: Methodsmentioning
confidence: 99%